An integrated surface coating strategy to enhance the electrochemical performance of nickel-rich layered cathodes. (January 2022) - Qu, Xingyu; Huang, He; Wan, Tao; Hu, Long; Yu, Zhenlu; Liu, Yunjian; Dou, Aichun; Zhou, Yu; Su, Mingru; Peng, Xiaoqi; Wu, Hong-Hui; Wu, Tom; et al.
Abstract: High-nickel layered oxides, LiNi x Co y Mn z O2 (0.6 ≤  x  < 1), are promising cathode materials for producing batteries with high energy density and working voltage, while their poor cycling performance severely limits their commercial applications. Herein, an integrated surface coating/doping strategy is developed to significantly improve the structural stability and electrochemical performance of LiNi0.88 Co0.06 Mn0.06 O2 . The titanium ions from a thin TiNb2 O7 coating layer diffuse inward during the high-temperature sintering process and a uniform protective layer forms on the surface of the secondary particles of the material. This protective layer suppresses side reactions, and the Ti 4+ doping increases the thickness of the lithium layer and reduces the lithium/nickel mixing, thereby enhancing the diffusion of lithium ions in bulk electrode. The capacity retention of modified material after 200 cycles at 1 C is greatly improved from 59.8% of the pristine material to 87.2%. First-principles calculations confirm the interaction affinity of the TiNb2 O7 coating on the layered LiNi0.88 Co0.06 Mn0.06 O2 with Ti ion migration in the interlayer region. Moreover, the enhanced oxygen release energy and electronic conductivity benefiting from Ti 4+ doping promote the cycling stability of the integrated cathode. The surface engineering strategy proposed herein is generally effective for the electrochemical improvement of nickel-rich ternary cathode materials. Graphical Abstract: Double-modified NCMs are obtained through facilely sintering the TNO-coated NCMs. Compared with Nb ions, Ti ions tend to diffuse into the NCM matrix. This work reveals that an appropriate amount of TNO coating effectively improves the structural stability and the electrochemical performance of NCM. ga1 Highlights: A new coating material, TiNb2 O7, was introduced for the first time to coat the nickel-rich layered ternary materials. During the modification process, the Ti element is more preferentially anchored in the NCM material than the Nb element. 1 wt% TiNb2 O7 -coated Li1.06 (Ni0.88 Co0.06 Mn0.06 )0.94 O2 displays excellent electrochemical performance. TiNb2 O7 -coating can effectively enhance the structural stability of nickel-rich layered ternary materials.